(untitled) (Research, Society and Development, 2021)
Objective: to characterize health professionals and biosafety conditions in coping with COVID-19 in Maceió- Al. Methodology: descriptive, cross-sectional study, with a quantitative approach and intentional non-probabilistic sampling technique. An electronic questionnaire was applied, elaborated through the Google Forms platform, with sociodemographic variables of the professional profile and questions that addressed opinions and work situations in the pandemic. The questionnaire was shared by messaging, social media and email apps. Results: 255 health professionals from different areas participated in the survey. Most professionals are young women with professional training in different categories, especially nursing. Most professionals have two jobs, with less than five years of training, a weekly workload of 60 or more hours and work predominantly in public institutions and in the hospital service. Among professionals, 42% have already had flu-like symptoms or confirmation of COVID-19. Regarding working conditions, 88% received PPE and guidance on biosafety in their workplaces, with the surgical mask being used most frequently. Conclusion: good conditions were observed for carrying out health work, however, it is necessary to outline coping strategies that take into account the singularities of each profession and the degree of exposure of the category.